Survey study on outdoor wideband system propagation of millimeter wave at 28-ghz in a 5g network system - Daho, Abdusalama; Abd. Rahman, Tharek; M Al-Samman, Ahmed; Yamada, Yoshihide (International Journal of Engineering and Technology, 2019)
High data rates up to 10 Gbps required on fifth generation (5G) wireless communication systems have targeted propagation studies of wireless channels with large bandwidths in millimeter wave spectrums of 28 GHz. Propagation studies cover the measurement, characterization and modelling of wireless channels that are used for testing and enhancement of 5G wireless communication systems. This study aims to contribute to this field by studying the radio wave propagation at 28 GHz for tropical regions, such as Malaysia. The work of this study included measuring, characterizing and modelling wideband channels for 5G wireless communications at the 28 GHz band. Extensive wideband channel measurement campaigns were conducted, to cover the outdoor environment in line-of-sight (LoS) and non-line-of-sight (NLoS) scenarios. Post-processing was also performed using SystemVue and MATLAB software to extract the power delay profile, path loss, angle of arrival (AOA) and root mean square (RMS) delay spread for every considered scenario to characterize the 5G channel. To make a more reliable and easier 5G channel characterization, the powerful propagation simulation, Wireless in Site software was also utilized to investigate all 5G-channel parameters and compare the simulation results with the measurement results. The findings from this study will contribute to the body of knowledge in this field through the development of a proposed model for the 5G channel in Malaysia at the 28 GHz band for the 5G system. Lastly, due to heavy rain in tropical regions, i.e. Malaysia, the wireless channel at high- frequency band should be further investigated in high rainfall regions to include measurement campaigns with different rain rate to investigate the signal degradation, power delay profile and delay spread with rain and compare it with clear air.Â Â